Water vapor heterogeneity related to tropopause folds over the North Atlantic revealed by airborne water vapor differential absorption lidar - Flentje, H.; Dörnbrack, A.; Ehret, G.; Fix, A.; Kiemle, C.; Poberaj, G.; Wirth, M. (Journal of Geophysical Research: Atmospheres, 2005)
ISSN:0148-0227 ISSN:2169-897X